LEVEL OF KNOWLEDGE OF SENIOR HIGH SCHOOL STUDENTS TO MANGROVE CONSERVATION: Fahmi Arif Kurnianto, Bejo Apriyanto , Elan Artono Nurdin , Fahrudi Ahwan Ikhsan - Fahmi Arif Kurnianto; Bejo Apriyanto; Elan Artono Nurdin; Fahrudi Ahwan Ikhsan (Geosfera Indonesia, 2017)
Geography Learning in XI Social Science Classes still dominated by conventional teaching methods that make students become unmotivated in learning. Therefore, it is necessary to apply a model of learning that can foster activity and student’s level of knowledge. The Group Investigation Learning model (GI) has several advantages. Advantages of Group Investigation Learning model among others: (1) increase the ability to think critically, (2) creating a learning environment that is democratic, (3) enhance the development of soft skills, (4) may improve social solidarity, dan (5) improve student’s level of knowledge to learn. The purpose of this study to analyze the influence of group investigation learning model towards the level of mangrove knowledge of students in senior high school. The type of research is the quasi-experimental study with non equivalent control group posttest only design. The subject of the study consisted of class XI Social Science are selected based on the score of Middle Semester Exam (UTS) 2 on 2014-2015 teachings year that had an average of almost the same (homogeneous).The results of this study are showed significant influence of GI models on Geography level of knowledge to learn of students. It was based on the results of the Independent Sample T-Test analysis showed a p-value of 0.000 level. P-level value is smaller than 0.05 (p <0.05). The average score student’s level of knowledge to learn geography experimental class is higher with a score of 208, while the control class w ith a score of 177. That's because the investigations conducted the mangrove forest, teachers simply deliver early learning problems, frequent interaction between students during learning, and students investigate different sub-themes. Keywords: Group Investigation Learning, Level of knowledge, mangrove Copyright (c) 2017 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License